Re imagining Performance Management - Sandeep Magavi (New Delhi Upkar Prakashan, 2022)
The best performing companies are shifting away from a rigid performance management system toward a more flexible approach that reinforces critical behaviors that matter every day and align individual work with organisational goals. Performance management has now evolved into finding ways to introspect & generate a growth mindset
Keywords: Performance Management